Development and implementation of «logging-while-drilling» technology in Ukraine. Methods and tools for determination of petrophysical parameters of reservoirs while drilling vertical, deviated and horizontal oil-and-gas boreholes - М.С. Бондаренко; В.В. Кулик; С.М. Данилів (Геофизический журнал, 2025)
Logging-while-drilling (LWD) oil-and-gas boreholes is an advanced technology that improves the efficiency of drilling-and-logging operations. The cost of services and the technological monopoly of foreign firms, and their leaving from Ukraine in 2022, make urgent the development of domestic apparatus-and-methodological complexes for LWD. The Group of Nuclear Geophysics of the Institute of Geophysics of the NAS of Ukraine, together with LLC «Ukrspetsprylad», have created a number of methods and tools for determining the petrophysical parameters of reservoirs during LWD. The effectiveness of the developments has been confirmed by borehole tests and comparison with independent data